Carbohydrate as a chiral template: optical resolution of N-tert-butanesulfinamides - Trang, Bui Thuy; Thuong, Cao Hai; Huu, Chu Chien (Vietnam Journal of Chemistry, 2017)
N-tert-butanesulfinamides, a class of amines bearing a sulfinyl group attached to nitrogen, exhibit pyramidal bonding where the non-bonded electron pair located at the sulfur atom acts as a fourth ligand. These compounds are configurationally sufficiently stable to be separated into R- and S- enantiomers. Enantiopure N-tert-butanesulfinamides are important auxiliaries in asymmetric synthesis, and some of them also have useful biological properties. In this paper, a new efficient strategy for enantioselective synthesis of N-tert-butanesulfinamides with very goods yields and excellent enantiomeric excess via the hydrolysis reaction of N-glycosidic bonds that were formed from D-ribose, under basic conditions was described. Keywords. N-tert-butanesulfinamide, N-glycoside, D-ribose, enantiomer, asymmetric synthesis.